2015
DOI: 10.1063/1.4936219
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic trajectory analysis of superparamagnetic beads driven by on-chip micromagnets

Abstract: We investigate the non-linear dynamics of superparamagnetic beads moving around the periphery of patterned magnetic disks in the presence of an in-plane rotating magnetic field. Three different dynamical regimes are observed in experiments, including (1) phase-locked motion at low driving frequencies, (2) phase-slipping motion above the first critical frequency f c1 , and (3) phase-insulated motion above the second critical frequency f c2 . Experiments with Janus particles were used to confirm that the beads m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…proteins [31]. Superparamagnetic beads on specially designed surfaces, which had a magnetic disk pattern, have been explored for potential use in cell separation for labon-a-chip [32]. These authors found a particle dynamics which looks similar to the one found in the present experiments, but the motion was limited to a small region around each magnetic disk of diameter 10-30 µm.…”
Section: Further Commentssupporting
confidence: 70%
“…proteins [31]. Superparamagnetic beads on specially designed surfaces, which had a magnetic disk pattern, have been explored for potential use in cell separation for labon-a-chip [32]. These authors found a particle dynamics which looks similar to the one found in the present experiments, but the motion was limited to a small region around each magnetic disk of diameter 10-30 µm.…”
Section: Further Commentssupporting
confidence: 70%
“…In these techniques, the beads usually act as labels. They can also be used as handles [3], for example to clean a solution [4] [5] or to deliver substances to a specific target [6]. In [7], it was shown that they can be used to enhance the adeno-associated viral vector delivery in human neural stem cell infection.…”
Section: Introductionmentioning
confidence: 99%
“…, a difference between the particle position on the disk perimeter and the external magnetic field angle). 41 At low frequencies ( i.e. , small phase lags), the particles experience a low phase lag and can follow the external field.…”
Section: Resultsmentioning
confidence: 99%